Designing Recolorization Algorithms to Help People with Color Vision Anomalies - V. V. Sinitsyna; A. M. Prudnik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The problem of perception of visual information by people with color vision anomalies remains quite relevant, as evidenced by the interest in studying this problem not only in medicine, but also in the field of medical technology. Researchers around are working on the task to create algorithms and software that can transform images and videos in accordance with their correct perception by people with color blindness. However, today there are no algorithms that allow people with any type, form, and degree of color vision anomaly to correctly perceive the visual information surrounding them. Based on the considered advantages and disadvantages of existing algorithms, conclusions were drawn about the requirements for the designed recoloring algorithms, which are planned to be implemented in software to help people with color perception issues. Such algorithms will not only allow correct video conversion for people with dichromacy and monochromacy but will also enable users with any degree of anomalous trichromacy to perceive the world around them most accurately. In addition, these algorithms will be distinguished by the high speed of the recolorization process, and the “naturalness” of the colors obtained in the process of transformations.